Acoustic Telemetry Around Western Australia’s Oil and Gas Infrastructure Helps Detect the Presence of an Elusive and Endangered Migratory Giant - Thomson, Paul G.; Pillans, Richard; Jaine, Fabrice R. A.; Harcourt, Robert G.; Taylor, Michael D.; Pattiaratchi, Charitha B.; McLean, Dianne L. (Frontiers in Marine Science, 2021)
Subsea infrastructure supporting the oil and gas and renewable energy industries can attract commercially important fish species as well as megafauna including sea lions, turtles, sharks, manta rays and whales. Potential impacts of this attraction, whether positive and negative, on migratory marine megafauna remain unknown. We deployed acoustic telemetry equipment around subsea infrastructure in a pilot study that aimed to assess its effectiveness in detecting visiting tagged marine animals and to understand how megafauna species may utilise these structures. We deployed acoustic receivers around four oil and gas platforms and on two remotely operated vehicles (ROVs) undertaking pipeline inspections on Australia’s North West Shelf. The ROV-attached receivers failed to detect any animals. However, two whale sharks (Rhincodon typus) previously tagged in the World Heritage Ningaloo Reef Marine Park were detected at two different platforms, North Rankin A and Pluto, located up to 340 km north of the initial tagging locations. The whale shark at North Rankin A visited the platform infrequently over ~6 weeks with a total of 15 detections. In contrast, the whale shark at Pluto platform was detected each day of the 24-day deployment, with a total of 4894 detections. Detections at Pluto platform were highest during the day, with peaks at dusk and dawn. Our lack of detections from the ROV pipeline surveys and other platforms probably reflect the small number of tagged animals in the region and a poor understanding of the range of the receivers in these environments. However, our pilot study indicates that acoustic telemetry around platforms may be an effective method for understanding how marine megafauna utilise these structures. We recommend collaborating with industry to undertake receiver range testing to better understand the effectiveness of the method. We further recommend that studies such as these should occur in parallel with intensive tagging programs at sites like Ningaloo Reef and around the structures themselves to maximise the probability of detections and improve our understanding of how marine megafauna use these structures.